CHEMICAL-THERMAL PROCESSING OF TRACTOR PARTS IN VACUUM AT APPLICATION OF TECHNOLOGY OF HARDENING IN THE MEDIUM OF INERT GASES - article editotial (Литьë и металлургия)
Advantages of technology of hardening by inert gases are considered. It is shown that use of unit ModulTherm7/1 at RUP «MTZ» allows to improve quality of chemical thermal processing of details and to provide decrease of expenses for manufacture.